ADVERTISING'S ELUSIVE ECONOMIC RATIONALE: PUBLIC POLICY AND TAXATION. (27th July 2015) - Driver, Ciaran
Abstract: Advertising and its effects have been debated for well over a century. In the last few decades a generally sceptical view of the benefits of advertising has been overturned by a series of academic advances in economics that detail a variety of ways in which advertising may affect the economy and society. This academic work has however been paralleled by a growing popular and political opposition to advertising and its social effects. In this paper, the positive economic case for advertising is challenged by an assessment of the main channels of its influence and by a review of the associated empirical findings on its economic and wider impact. A policy response of limiting the tax deductibility of business advertising is explored.